2001
DOI: 10.1016/s1097-2765(01)00190-3
|View full text |Cite
|
Sign up to set email alerts
|

TRAPP I Implicated in the Specificity of Tethering in ER-to-Golgi Transport

Abstract: TRAPP is a conserved protein complex required early in the secretory pathway. Here, we report two forms of TRAPP, TRAPP I and TRAPP II, that mediate different transport events. Using chemically pure TRAPP I and COPII vesicles, we have reconstituted vesicle targeting in vitro. The binding of COPII vesicles to TRAPP I is specific, blocked by GTPgammaS, and, surprisingly, does not require other tethering factors. Our findings imply that TRAPP I is the receptor on the Golgi for COPII vesicles. Once the vesicle bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
354
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(376 citation statements)
references
References 45 publications
18
354
2
2
Order By: Relevance
“…Alternatively, these proteins and the phosphoinositides generated by their action may play additional roles during meiosis. Consistent with the idea that trafficking is important for meiosis, gsg1 mutants are defective in meiotic division , and recent work has indicated that Gsg1p is the high-molecular-weight subunit of both the TRAPP I complex, involved in vesicle-mediated transport from the ER to the Golgi, and the TRAPP II complex, involved in intra-Golgi trafficking (Sacher et al, 2000(Sacher et al, , 2001. Mutations in SPO15/VPS1, which encodes a dynamin-like protein required for sorting of proteins from the Golgi to the vacuole, also fail to undergo meiotic division (Yeh et al, 1991).…”
Section: Phosphoinositide Function During Meiosismentioning
confidence: 68%
“…Alternatively, these proteins and the phosphoinositides generated by their action may play additional roles during meiosis. Consistent with the idea that trafficking is important for meiosis, gsg1 mutants are defective in meiotic division , and recent work has indicated that Gsg1p is the high-molecular-weight subunit of both the TRAPP I complex, involved in vesicle-mediated transport from the ER to the Golgi, and the TRAPP II complex, involved in intra-Golgi trafficking (Sacher et al, 2000(Sacher et al, , 2001. Mutations in SPO15/VPS1, which encodes a dynamin-like protein required for sorting of proteins from the Golgi to the vacuole, also fail to undergo meiotic division (Yeh et al, 1991).…”
Section: Phosphoinositide Function During Meiosismentioning
confidence: 68%
“…The exocyst (sec6/8 complex), composed of eight proteins, is thought to help recruit Golgiderived vesicles to the plasma membrane at the final step of the secretory pathway (Hsu et al, 1996;TerBush et al, 1996;Kee et al, 1997). The multisubunit TRAPP I and Vps52/ 53/54 complexes are believed to serve analogous functions during ER-to-Golgi and endosome-to-Golgi trafficking, respectively (Conibear and Stevens, 2000;Sacher et al, 2001). The eight-component mammalian conserved oligomeric Golgi (COG) complex and the homologous Sec34/35 complex in yeast have been proposed to assist in Golgi vesicle targeting VanRheenen et al, 1998;Walter et al, 1998;VanRheenen et al, 1999;Sacher et al, 2001;Whyte and Munro, 2001;Ungar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The multisubunit TRAPP I and Vps52/ 53/54 complexes are believed to serve analogous functions during ER-to-Golgi and endosome-to-Golgi trafficking, respectively (Conibear and Stevens, 2000;Sacher et al, 2001). The eight-component mammalian conserved oligomeric Golgi (COG) complex and the homologous Sec34/35 complex in yeast have been proposed to assist in Golgi vesicle targeting VanRheenen et al, 1998;Walter et al, 1998;VanRheenen et al, 1999;Sacher et al, 2001;Whyte and Munro, 2001;Ungar et al, 2002). The COG complex can stimulate intra-Golgi trafficking in vitro (Walter et al, 1998), and subunits of the Sec34/35 complex have been shown to be required for ER-to-Golgi trafficking, retrograde transport through the Golgi, and trafficking between the Golgi and endosomes (Spelbrink and Nothwehr, 1999;VanRheenen et al, 1999;Whyte and Munro, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian homologues of the VFT⅐GARP complex are identified and could function similarly as tethering proteins in the trans-Golgi network (20). TRAPPI and -II are two related tethering complex that function in endoplasmic reticulum-Golgi and intra-Golgi transport and act together with Ypt1/Rab1 (21), whereas the HOPS complex (or Class C VPS complex) consisting of Vps11, Vps16, Vps18, Vps33, Vps39, and Vps41 act together with Ypt7 and SNAREs in mediating tether and fusion at the vacuole in yeast (22). The HOPS complex has been shown to function in multiple transport steps in addition to fusion at the vacuolar membrane (23)(24).…”
mentioning
confidence: 99%